(3MGTjI ejQ CHj GdaJM Ydi BOGH YVO GdOjfs - (3GdSYjOj, GdCQOHjdj, CHh GdaJM, eMeO Hf Cejf, cGf MjG bHd (B875 (3g`s ((3MRfjs)
(3ChdgG (B:s
(3GdMeO ddg Ydi GagGe GdNWGH agPg aGFOI YLGH Hd RGFOI dG JONd aj GdMSGH Ydi GdTQM GdeTghQ Hjf Chdj GdCdHGH ddQSGdI GdTQjaI GdYVOjI aj GdBOGH JcTa Yf hLhg ebGUOg GdfbGHs
(3BNQgG (B:s
(3bhdg GYde Cf GdMhGTj Cg` hGYde Gf eG fbd efg aj MhGTj gPG GdTQM deG cGfJ eXHhWI eYJeOG YdjgG YfOj GdJReJ GdETGQI EdjgG aj ehGVYgG djYJeO YdjgG GdeMUdhf hjejR Yf ZjQgG GdWGdHhf JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3/142s
(3cTa GdXfhf (B1/41s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs